Definition and quantification of 'ride' during running. (4th May 2018) - Lam, Christopher Ka-Yin; Mohr, Maurice; Nigg, Sandro; Nigg, Benno
Abstract: 'Ride' is a term that has been used occasionally to describe the feel of a shoe while running, yet it has never formally been defined nor have there been any suggestions of how to objectively measure 'ride'. In this study, we proposed a definition for 'ride', relating to the smoothness of the transition of the foot through the stance phase of gait, and suggested that the peak velocity in the anterior–posterior direction derived from the centre of pressure would be an appropriate measure to quantify 'ride'. Then, we used experimental evidence to advocate the appropriateness of this assessment. Thirteen participants ran over 160 metres in two pairs of shoes with different midsole compliance, and subjectively evaluated the 'ride' and comfort of each shoe. Centre of pressure was measured from pressure-sensing insoles and the peak velocity in the anterior–posterior direction was taken from the transition from heel to forefoot. It was found that individuals were able to perceive the 'ride' of a shoe and the shoe with the lower peak velocity coincided with a significantly higher rating of 'ride' and comfort ( p < 0.001). However, it was not always the shoe with the softer midsole that had a smoother 'ride', as 5 out of 13 participants had a smoother 'ride' in the stiff midsole. Further research is required to understand why certain individuals have a smoother 'ride' in a compliant versus a stiff midsole. This concept could prove useful in the real world and could possibly be implemented within a shoe store to help guide the selection of a shoe.